INVESTIGATION OF THE ELEMENTAL COMPOSITION OF SAMPLES OF THE PLANT PRUNUS CERASUS L. FROM THREE DISTRICTS OF THE FERGHANA REGION USING THE ICP-MS METHOD. (Scientific journal of the Fergana State University, 2024)
Using the modern ICP-MS method, the amount of elements in leaves and pips of the Cherry (Prunus cerasus L.) plant was studied for the first time. In different samples 44-46 elements were determined. In the three samples studied, a common pattern was observed: minerals were more abundant in leaves than in pips (leaves: 24908.248-49033.50; pips: 16277.862-28949.076 mg/kg). Samples from Altiarik and Tashlak contain significantly more elements compared to samples from Baghdad. Comparison of the amounts of only three macronutrients (Na+Mg+K) shows that the difference in the total amount of all elements is due to these three elements; Tashlak leaves 26620 mg/kg, Altiarik leaves 29700 mg/kg, Baghdad leaf 9963 mg/kg. Probably, the application of potassium fertilizers to the soil led to an increase in the amount of this element in Tashlak and Altiarik samples. Among macronutrients, the highest amount of potassium was also recorded in samples of foreign cherry, and the amounts of trace elements within the error of the experiment are close to each other in both foreign and our studied samples.